Implementation of a Structured Inquiry Learning Model Based on Local Wisdom to Improve Junior High School Students' Science Process Skills - Nurisma Noviana; Beni Setiawan; Mohammad Romadhoni (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Science process skills (SPS) are an important aspect in science learning that allows students to master basic science skills through direct experience. Low students' science process skills are often caused by theoretical learning and less relevant to the context of everyday life. This study aims to determine the effectiveness of the structured inquiry learning model based on local wisdom in improving students' SPS on food nutrition material. This study is a pre-experimental study with a one-group pretest-posttest design. The research subjects consisted of 36 students of class VIII-C of SMP Negeri 1 Jetis Ponorogo who were selected by purposive sampling. Data collection procedures were carried out through observation of learning implementation, SPS tests (pretest and posttest), and student response questionnaires. Data analysis techniques used descriptive analysis for model implementation and student responses, while the improvement of SPS was analyzed using another non-parametric Wilcoxon test and N-gain score calculation. The results showed that the implementation of the structured inquiry model based on local wisdom was categorized as very high. Statistical analysis showed a significant difference between the pretest and posttest results, with an N-gain score of 0.84 in the high category. Furthermore, students responded very positively to the integration of local wisdom into learning. In conclusion, the structured inquiry model based on local wisdom is effective in significantly improving students' science process skills. These findings recommend the use of local cultural contexts as a means to facilitate more contextual and meaningful science learning at the secondary school level